Diaphyseal nutrient foramina in the humerus, radius, femur, and tibia bones of mixed breed dogs (Journal of Advanced Veterinary and Animal Research, 2021)
Objective: The objective of this study was to determine the location, number, and direction of the nutrient foramen in the humerus, radius, femur, and tibia bones of mixed breed dogs.  Materials and Methods: The humerus, radius, femur, and tibia of both (left and right) limbs of mixed breed dogs were examined in this study. The number, location, and direction of the nutrient foramina were identified. Once identified, the diameter of each nutrient foramen was measured and the site index calculated.  Results: Only one nutrient foramen was identified in the humerus, radius, tibia, and right femur, while the foramen numbers ranged from one to three in the left femurs examinated. The nutrient foramen was localized on the caudal surface in the radii, femurs, tibias, and left humeri. Contrasting, however, 75% were located on the caudal surface of the right humeri and 25% on the lateral surface. The average diameter of the nutrient foramen of the humerus ranged from 0.88 to 1.00 mm, while it ranged from 1.13 to 1.25 mm in the radius. On the hind limb, the diameter of the nutrient foramen on the femur ranged from 1.2 to 1.3 mm and 0.75–1.25 mm on the tibia. The nutrient foramen was directed towards the corresponding joint in 100% of the humeri and tibias, 75% of the radii, and 60%–80% of the femurs examined.  Conclusion: The anatomical data on the nutrient foramen obtained in this study will be valuable for veterinarians when diagnosing pathological bone lesions and for orthopedic surgery.J. Adv. Vet. Anim. Res., 8(2): 203-209, June 2021